Controversies Over Cross-Religious Greetings: Fatwa Discourse and Religious Moderation in Indonesia - Arsal; Imran, Maizul (Moderatio: Jurnal Moderasi Beragama, 2025)
This study examines the legal status of cross-religious greetings through a textual legal interpretation analysis based on fatwas and the concept of religious moderation. This practice, often observed in official events, has sparked significant debate among Muslim scholars and government officials. The controversy escalated following a fatwa issued by the East Java Indonesian Ulama Council (MUI), which declared cross-religious greetings haram due to concerns about the potential mixing of beliefs. This stance was countered by the Ministry of Religious Affairs, which argued that such greetings promote interreligious harmony and are therefore permissible. Employing a literature-based approach and legal interpretation theory, this research provides an academic perspective without intending to discredit any party. The study concludes that cross-religious greetings are permissible (mubah) when intended to uphold national harmony and religious pluralism. It highlights the importance of balancing adherence to religious principles with the need for societal unity and coexistence in a pluralistic nation.